Effect of Subthalamic Stimulation on Voice and Speech in Parkinson’s Disease: For the Better or Worse? - Skodda, Sabine; Groenheit, Wenke; Schlegel, Uwe; Suedmeyer, Martin; Schnitzler, Alfons; Wojtecki, Lars (Frontiers in Neurology, 2014)
Background: Deep brain stimulation of the subthalamic nucleus, although highly effective for the treatment of motor impairment in Parkinson´s disease, can induce speech deterioration in a subgroup of patients. The aim of the current study was to survey 1) if there are distinctive stimulation effects on the different parameters of voice and speech and 2) if there is a special pattern of preexisting speech abnormalities indicating a risk for further worsening under stimulation. Methods: N = 38 patients with Parkinson´s disease had to perform a speech test without medication with stimulation ON and OFF. Speech samples were analysed: 1) according to a four-dimensional perceptual speech score and 2) by acoustic analysis to obtain quantifiable measures of distinctive speech parameters. Results: Quality of voice was ameliorated with stimulation ON, and there were trends to increased loudness and better pitch variability. N = 8 patients featured a deterioration of speech with stimulation ON, caused by worsening of articulation or/and fluency. These patients had more severe overall speech impairment with characteristic features of articulatory slurring and articulatory acceleration already under StimOFF condition. Conclusion: The influence of subthalamic stimulation on Parkinsonian speech differs considerably between individual patients, however, there is a trend to amelioration of voice quality and prosody. Patients with stimulation-associated speech deterioration featured higher overall speech impairment and showed a distinctive pattern of articulatory abnormalities at baseline. Further investigations to confirm these preliminary findings are necessary to allow neurologists to pre-surgically estimate the individual risk of deterioration of speech under stimulation.